2006
DOI: 10.1111/j.0303-6987.2006.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard and experimental therapy in cutaneous T‐cell lymphomas

Abstract: Cutaneous T-cell lymphomas are a heterogeneous group of lymphoproliferative disorders, characterized by the accumulation of clonal lymphocytes in the skin. Skin-directed therapies are the preferred first-line modalities. There are interesting new developments in topical therapy using retinoids and gene-therapy products such as adenovirus- interferon (IFN)-gamma. Systemic treatment uses biologicals such as fusion molecules, monoclonal antibodies and immune response modifiers (IFNs and retinoids), and well-toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Immunotherapy is one such solution that currently belongs to the standard therapeutic armamentarium. The use of recombinant cytokines has found its rationale in the immunobiology of this disease group and aims to enhance antitumor immunity (1,2). As an alternative to recombinant cytokines that are often associated with significant systemic side effects, we recently described adenovirusmediated (Ad-mediated) delivery of human IFN-γ gene directly into CL lesions, showing good tolerability together with promising efficacy (3).…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy is one such solution that currently belongs to the standard therapeutic armamentarium. The use of recombinant cytokines has found its rationale in the immunobiology of this disease group and aims to enhance antitumor immunity (1,2). As an alternative to recombinant cytokines that are often associated with significant systemic side effects, we recently described adenovirusmediated (Ad-mediated) delivery of human IFN-γ gene directly into CL lesions, showing good tolerability together with promising efficacy (3).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, primary cutaneous lymphomas have been successfully treated clinically with recombinant IFNs, counterbalancing the Th2-skewing state [34]. The short half-lives and toxic effects of these recombinant proteins have prompted preclinical studies involving interferon gene transfer methods to elicit similar effects on tumor growth [32,35,36].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Patients with mycosis fungoides and Sézary syndrome in its early stages are generally treatable. However, although treatment leads to partial or total remission, it cannot result in final cure of the disease [82] . Transcriptional profiling of mycosis fungoides and the Sézary syndrome identified that NF κ B and STAT factors and their signal transduction pathways play a critical role in the pathogenesis of these malignancies [83] .…”
Section: Curcumin and Cutaneous T-cell Lymphomamentioning
confidence: 99%